GM-CSF Expression and Macrophage Polarization in Joints of Undifferentiated Arthritis Patients Evolving to Rheumatoid Arthritis or Psoriatic Arthritis - Fuentelsaz-Romero, Sara; Cuervo, Andrea; Estrada-Capetillo, Lizbeth; Celis, Raquel; García-Campos, Raquel; Ramírez, Julio; Sastre, Sergi; Samaniego, Rafael; Puig-Kröger, Amaya; Cañete, Juan D. (Frontiers in Immunology, 2021)
Background and Aims GM-CSF-dependent macrophage polarization has been demonstrated in rheumatoid arthritis (RA). Our aim was to seek diagnostic/prognostic biomarkers for undifferentiated arthritis (UA) by analyzing GM-CSF expression and source, macrophage polarization and density in joints of patients with UA evolving to RA or PsA compared with established RA or PsA, respectively. Methods Synovial tissue (ST) from patients with UA evolving to RA (UA>RA, n=8), PsA (UA>PsA, n=9), persistent UA (UA, n=16), established RA (n=12) and PsA (n=10), and healthy controls (n=6), were analyzed. Cell source and quantitative expression of GM-CSF and proteins associated with pro-inflammatory (GM-CSF-driven) and anti-inflammatory (M-CSF-driven) macrophage polarization (activin A, TNFα, MMP12, and CD209, respectively) were assessed in ST CD163+ macrophages by multicolor immunofluorescence. GM-CSF and activin A levels were also quantified in paired synovial fluid samples. CD163+ macrophage density was determined in all groups by immunofluorescence. Results Synovial stromal cells (FAP+ CD90+ fibroblast, CD90+ endothelial cells) and CD163+ sublining macrophages were the sources of GM-CSF. ST CD163+ macrophages from all groups expressed pro-inflammatory polarization markers (activin A, TNFα, and MMP12). Expression of the M-CSF-dependent anti-inflammatory marker CD209 identified two macrophage subsets (CD163+ CD209high and CD163+ CD209low/-). CD209+ macrophages were more abundant in ST from healthy controls and PsA patients, although both macrophage subtypes showed similar levels of pro-inflammatory markers in all groups. In paired synovial fluid samples, activin A was detected in all patients, with higher levels in UA>RA and RA, while GM-CSF was infrequently detected. ST CD163+ macrophage density was comparable between UA>RA and UA>PsA patients, but significantly higher than in persistent UA. Conclusions GM-CSF is highly expressed by sublining CD90+ FAP+ synovial fibroblasts, CD90+ activated endothelium and CD163+ macrophages in different types of arthritis. The polarization state of ST macrophages was similar in all UA and established arthritis groups, with a predominance of pro-inflammatory GM-CSF-associated markers. CD163+ macrophage density was significantly higher in the UA phases of RA and PsA compared with persistent UA. Taken together, our findings support the idea that GM-CSF is a strong driver of macrophage polarization and a potential therapeutic target not only in RA but also in PsA and all types of UA.